Integrated approach to explore Anemonia viridis regeneration under a climate change scenario - Claudia La Corte; Stephanie Barnay-Verdier; Paola Furla; Luca Bisanti; Mariano Dara; Gabriele Rizzuto; Salvatrice Vizzini; Maria Giovanna Parisi; Matteo Cammarata (Scientific Reports)
Abstract This study investigates the mechanisms of regeneration in Anemonia viridis under natural conditions and thermal stress, addressing the question: “Does an anthozoan subjected to thermal stress regenerate similarly to one experiencing only a wound?“. Oxidative stress markers (protein carbonylation, total antioxidant capacity) and symbiont photosynthetic efficiency (via Pulse Amplitude Modulation) were analyzed. Key proteins related to inflammation and tissue regeneration, including toll-like receptor, nuclear factor kappa B, heat shock proteins, and interleukin-1β, were examined using blotting techniques. Observations revealed higher antioxidant capacity at 20 °C than 27 °C after 6- and 24-hours post-injury. Thermal stress disrupted redox balance, as indicated by decreased symbiont photosynthetic efficiency. Protein expression analyses (proliferating cell nuclear antigen, heat shock protein 90, collagen Type XXIV α1) showed activation of compensatory mechanisms, but oxidative stress biomarkers highlighted significant cellular stress. These results suggest that elevated temperatures may impair regeneration in Anemonia viridis, highlighting a potential vulnerability of anthozoans to thermal stress associated with climate change.